Downstream Swimming Behaviour of Catadromous and Potamodromous Fish Over Spillways. (13th May 2015) - Silva, A. T.; Katopodis, C.; Tachie, M. F.; Santos, J. M.; Ferreira, M. T.
Abstract: Flow characteristics associated with spillways are important to restore ecological connectivity because spillways can either constrain or offer safe routes for downstream passage of fish. We studied the hydrodynamics of flow and downstream movement behaviour of the catadromous European eel ( Anguilla anguilla ) and the potamodromous Iberian barbel ( Luciobarbus bocagei ) in spillways with upstream face inclinations of θ  = 90° (standard) 45° and 30° (modified). The standard spillway was tested for two water depths ( H  = 32 and 42 cm). Modified spillways facilitated downstream passage and reduced delay times of passage of the European eel. Upstream of the 90° spillway, distinct recirculation areas were observed, and associated turbulence strongly hampered downstream passage of fish. Both species were found to avoid turbulence, but barbel displayed stronger avoidance for areas of rapid changes in flow velocity when comparing to eels. Overall, eels were faster in passing the spillway and had a higher downstream passage success (80%) than barbel (32%). Eels were predominantly thigmotactic in contrast to barbel, which showed limited contact with structures. The results suggest that modified spillways may enhance passage survival. Copyright © 2015 John Wiley & Sons, Ltd.